Determining the initial spatial extent of an environmental impact assessment with a probabilistic screening methodology. (November 2018) - Peeters, Luk J.M.; Pagendam, Daniel E.; Crosbie, Russell S.; Rachakonda, Praveen K.; Dawes, Warrick R.; Gao, Lei; Marvanek, Steve P.; Zhang, YongQiang; McVicar, Tim R.
Abstract: A crucial decision in defining the scope of an environmental impact assessment is to delineate the initial assessment area. We developed a probabilistic methodology to determine this area, which starts by identifying a key environmental variable, maximum acceptable change and acceptable probability of exceeding that threshold. The exceedance probability is determined with a limits of acceptability rejection sampling of informed prior parameter distributions. A qualitative uncertainty analysis, a formal and systematic discussion of the main assumptions and model choices, is complemented with global sensitivity analysis of the model results to identify the major sources of uncertainty and provide guidance for further research and data collection. For the case study on coal development in the Gloucester Basin (NSW, Australia), the initial assessment extent is unlikely to extend more than 5 km from the edge of the planned coal mines. The major source of uncertainty is the planned mine water production rate. Highlights: Probabilistic methodology to systematically account for uncertainty during early stages of environmental impact assessment. Define type of impact, threshold of acceptable change and acceptable probability of exceedance. Quantitative uncertainty analysis to estimate zone of potential change based on threshold exceedance probability. Sensitivity analysis and qualitative uncertainty analysis to understand and communicate sources of uncertainty.